INFLATIONARY THRESHOLD AND ECONOMIC GROWTH IN NIGERIA - OBUTE, CHRISTOPHER OBILIKWU; ASUE, EMMANUEL AONDONGUSHA; IKYAATOR, JAMES VAACHIA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2020)
This paper estimates inflationary threshold in Nigeria using all the components of the aggregate demand model. The study used annual time series from 1981 to 2019 and the variables were confirmed to be free from unit root problems using Augmented Dickey Fuller and Ng-Perron Tests. The bounds test results suggested that there was long run relationship among the variables while the short run error correction model showed that the variables were capable of adjusting back to equilibrium in an event of any temporary shock within a year. The study found that the inflationary threshold for Nigeria is 8%. This is because the residual sum of squares was at maximum at 8% while the sum of the coefficients of inflation and the constructed dummy variable remained highest at 8%. It was therefore recommended among other things that central bank of Nigeria should gear its inflation target towards 8%.